(untitled) (Texas Journal of Philology, Culture and History, 2023)
In this article, language and period-specific terms are explained; the study of period-specific relations and their importance in linguistics, the role of linguistic tools expressing the period relationship in the text are analyzed on the example of excerpts from various works.